2016
DOI: 10.1101/gr.192526.115
|View full text |Cite
|
Sign up to set email alerts
|

An extended set of yeast-based functional assays accurately identifies human disease mutations

Abstract: We can now routinely identify coding variants within individual human genomes. A pressing challenge is to determine which variants disrupt the function of disease-associated genes. Both experimental and computational methods exist to predict pathogenicity of human genetic variation. However, a systematic performance comparison between them has been lacking. Therefore, we developed and exploited a panel of 26 yeast-based functional complementation assays to measure the impact of 179 variants (101 disease-and 78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
139
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 88 publications
9
139
1
1
Order By: Relevance
“…Although each is an imperfect measure of the functionality of amino acid changes (Sun et al , 2016), each should and did correlate with DMS results (Fig 1D top panel, Appendix Fig S1). Finally, we confirmed that, as expected, amino acid residues on the protein surface are more tolerant to mutation than those in the protein core or within interaction interfaces (Fig 1D, bottom panel).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Although each is an imperfect measure of the functionality of amino acid changes (Sun et al , 2016), each should and did correlate with DMS results (Fig 1D top panel, Appendix Fig S1). Finally, we confirmed that, as expected, amino acid residues on the protein surface are more tolerant to mutation than those in the protein core or within interaction interfaces (Fig 1D, bottom panel).…”
Section: Resultsmentioning
confidence: 88%
“…For Stage 3—selection for clones encoding a functional protein—we employed a S. cerevisiae functional complementation assay (Jiang & Koltin, 1996; Sun et al , 2016), based on human UBE2I 's ability to rescue growth at an otherwise‐lethal temperature in a yeast strain carrying a temperature‐sensitive (ts) allele of the UBE2I ortholog UBC9 . Despite a billion years of divergence, yeast functional complementation assays can accurately discriminate pathogenic from non‐pathogenic human variants (Sun et al , 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations